Thermodynamics of ion pair conversion in alcohol solutions of hydrogen chloride - Bulavin, Viktor Ivanovych; V'unik, Ivan Nikolajevych; Kramarenko, Andrii Viktorovych; Rusinov, Alexandr Ivanovych (Національний технічний університет "Харківський політехнічний інститут", 2022)
The thermodynamic quantities of the dissociation stages of contact ion pairs (CIP) and solvent-separated ion pairs (SSIP) into ions, conversion of CIP into SSIP of the ionization process of HCl in n-alcohols from methyl to n-octyl at 278.15 – 328.15 K, i.e. in non-aqueous solvents that are most frequently used in chemical research and in chemical technology have been calculated. The proton and chloride ion forming HCl are modeled in a comparative study of the solvation process and the molecular mechanism of acid ionization in various solvents, which emphasizes the relevance of this study, in which the influence of the nature of the solvent, hydrogen chloride ions and temperature on the above thermodynamic quantities are considered. The calculation of the dissociation constants of CIP was carried out according to Ebeling’s equation, which takes into account the short range repulsive forces between the ions in the ion pair and the dispersion interactions between the solvent molecules. The dissociation constants and thermodynamic quantities of SSIPs have been calculated by the Schwartz method, which evaluates the physical and chemical parameters of the solvent (besides the dielectric permittivity also the free volume of the solvent molecules, isothermal compressibility, etc.) that significantly affect the properties of ion pairs. The main conclusions drawn from our analysis of the array of thermodynamic data on the ionization stages of HCl in n alcohols from methyl to n-octyl: (a) in methanol the predominant among the ion pairs are SSIPs, in ethanol the concentration of CIPs and SSIPs is approximately the same, and in other alcohols, the CIPs predominate; b) the concentration of CIPs increases with increasing alkyl radical of the alcohol when passing from methanol to n-octanol respectively from 30% to 95%; c) ratio of enthalpic (ΔconvH°) and entropic (–TΔconvS°) factors in methanol and ethanol ensures spontaneous conversion of CIP to SSIP; d) in alcohols from n-propyl to n-octyl values and sign ΔG° for the stages of dissociation of CIP and SSIP into ions and conversion of CIP to SSIP are determined by the entropic term (–ТΔS°), which leads to deconversion of ion pairs, i.e., the conversion of SSIPs into CIPs

Проведено розрахунок термодинамічних характеристик стадій дисоціації контактних іонних пар (КІП) та розділених розчинником іонних пар (РІП) на іони, конверсії КІП у РІП процесу іонізації HCl в н-спиртах від метилового до н-октилового при 278,15 – 328,15 К , тобто у неводних розчинниках, які найчастіше використовуються при хімічних дослідженнях та у хімічній технології. Протон та хлорид-іон, що утворюють HCl, є модельними при порівняльному дослідженні процесу сольватації та молекулярного механізму іонізації кислот у різних розчинниках, що наголошує на актуальності даного дослідження, в якому розглянуто вплив природи розчинника, іонів хлороводню та температури на зазначені вище термодинамічні характеристики. Розрахунок констант дисоціації КІП проводили за рівнянням Ебелінга, що враховує короткодіючі сили відштовхування між іонами в іонній парі та дисперсійні взаємодії між молекулами розчинника. Константи та термодинамічні характеристики дисоціації РІП обчислювали за методикою Шварца, в якій враховуються фізико-хімічні параметри розчинника (крім діелектричної проникності також вільний об’єм молекул розчинника, ізотермічна стисливість та ін.), що істотно впливають на властивості іонних пар. Основні висновки, зроблені на підставі аналізу отриманого нами масиву термодинамічних даних щодо стадій іонізації HCl в н-спиртах від метилового до н-октилового: а) в метанолі серед іонних пар переважають РІП, в етанолі концентрація КІП і РІП приблизно однакова, а в інших спиртах переважають КІП; б) концентрація КІП зі зростанням алкільного радикала спирту збільшується при переході від метанолу до н-октанолу відповідно від 30 до 95%; в) співвідношення ентальпійного (ΔконвH°) та ентропійного (–TΔконвS°) факторів у метанолі та етанолі сприяє самочинній конверсії КІП у РІП; г) у спиртах від н-пропілового до н октилового значення та знак ΔG° для стадій дисоціації КІП і РІП на іони та конверсії КІП у РІП визначаються ентропійною складовою (–ТΔS°), що призводить до деконверсії іонних пар, тобто перетворення РІП на КІП.
Термодинаміка конверсії іонних пар у спиртових розчинах хлороводню
Keywords: ion pairs; proton; conversion; hydrogen chloride; primary alcohols; acids ionization; іонні пари; протон; конверсія; хлороводен; н-спирти; іонізація кислот